Synthesis, physical-chemical properties and further transformation of 5-(quinoline-2-yl, 2-hydroxyquinoline-4-yl)-4-R-2,4-dyhydro-3Н-1,2,4-triazole-3-thiones - T. M. Kaplaushenko (Zaporozhye State Medical University, 2016)
The aim of this work was the synthesis of new highly effective and low-toxic substances in a series of 5-(quinoline-2-yl, 2-hydroxyquinoline-4-yl)-4-R1-2,4-dyhydro-3Н-1,2,4-triazole-3-thiones and its derivatives, and also establishment of physical-chemical properties of all synthesized compounds, as well as computer predictions. Materials and methods. As starting compounds we used esters of quinoline-2 and 2-hydroxyquinoline-4-carboxylic acids, which through a series of successive stages (reaction of hydrazinolysis, electrophilic substitution and intramolecular basic heterocyclization) have been transformed to 5-(quinoline-2-yl, 2-hydroxyquinoline-4-yl)-4-R1-2,4-dyhydro-3Н-1,2,4-triazole-3-thiones and their derivatives. 2-(5-(Quinoline-2-il-, 2-hydroxyquinoline-4-yl)-4-R1-2,4-dyhydro-3Н-1,2,4-triazole-3-ylthio)aceto-nitriles have been synthesized in a propanol medium with heating. The synthesized compounds have been crystallized using ethanol. Physical and chemical properties of all the obtained compounds have been investigated, their structure has been proved by elemental analysis, IR spectroscopy, 1H NMR spectroscopy, UV spectrophotometry and chromatography-mass-spectrometry . Individuality of synthesized compounds has been installed using chromatographic methods of analysis. As the result of made work, the preliminary computer study on acute toxicity and biological activity has been done. Results. While synthetic studies 9 new, indescribable earlier compounds have been obtained. According to analysis of computer prediction, which was conducted using PASS online service, it has been found that synthesized 5-(quinoline-2-yl, 2-hydroxyquinoline-4-yl)-4-R1-2,4-dyhydro-3Н-1,2,4-triazole-3-thiones and their derivatives are low-toxic compounds, and exhibit wide range of biological effects, which in its turn corresponds to the literature data. As a result of this work the most promising compounds are selected for testing in vitro. Conclusion. As a result of the work the structure of the synthesized compounds has been confirmed, which in its turn indicates the possibility of their further use in biological research.